Sighs and Signs of the Spirit: Ghanaian Perspectives on Pentecostalism and Renewal in Africa - Asamoah-Gyadu, J. Kwabena (Regnum; Wipf and Stock, 2015)
J. Kwabena Asamoah Gyadu "offers his reader a comprehensive and highly perceptive account of the appeal and theological influence of this kind of Christianity, combining scholarly excellence with a deep insider understanding of resonances with African religious sensibilities." Martin Lindhardt (From the Foreword)
Free